2008
DOI: 10.1016/j.gca.2008.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Zn-rich phyllosilicate, Zn-layered double hydroxide and hydrozincite in contaminated calcareous soils

Abstract: Recent studies demonstrated that Zn-phyllosilicate-and Zn-layered double hydroxide-type (Zn-LDH) precipitates may form in contaminated soils. However, the influence of soil properties and Zn content on the quantity and type of precipitate forming has not been studied in detail so far. In this work, we determined the speciation of Zn in six carbonate-rich surface soils (pH 6.2 to 7.5) contaminated by aqueous Zn in the runoff from galvanized power line towers (1322 to 30090 mg/kg Zn). Based on 12 bulk and 23 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 55 publications
9
90
1
Order By: Relevance
“…In the current study, we did not detect these species in the soils GUR and LIE with near-neutral pH. This may be due to relatively low Zn levels compared to the previously studied heavily contaminated soils, but may also reflect the limited long-term stability of these phases in the soil environment (Voegelin et al, 2002;Voegelin and Kretzschmar, 2005;Jacquat et al, 2008). As reported by Paquet et al (1986), trioctahedral Zn-rich smectites from ore deposits are unstable upon weathering and evolve to dioctahedral smectites with low Zn contents and finally to Zn-kaolinite and Zn-containing Fe (hydr)oxides.…”
Section: Pedogenic Zn-speciescontrasting
confidence: 66%
“…In the current study, we did not detect these species in the soils GUR and LIE with near-neutral pH. This may be due to relatively low Zn levels compared to the previously studied heavily contaminated soils, but may also reflect the limited long-term stability of these phases in the soil environment (Voegelin et al, 2002;Voegelin and Kretzschmar, 2005;Jacquat et al, 2008). As reported by Paquet et al (1986), trioctahedral Zn-rich smectites from ore deposits are unstable upon weathering and evolve to dioctahedral smectites with low Zn contents and finally to Zn-kaolinite and Zn-containing Fe (hydr)oxides.…”
Section: Pedogenic Zn-speciescontrasting
confidence: 66%
“…Despite the similar low SPOIL value of Zn(OH) 2 and hydrozincite, Zn(OH) 2 was never detected by LCF. We attribute this to the much higher solubility of Zn(OH) 2 (and hydrozincite) than of Zn-LDH and trioctahedral Znphyllosilicates under soil chemical conditions (Ford and Sparks, 2000;Panfili et al, 2005;Jacquat et al, 2008).…”
Section: Lcf Analysis Of Soil Exafs Spectramentioning
confidence: 96%
“…Details on most synthesis procedures have previously been reported Voegelin et al, 2005;Jacquat et al, 2008;Jacquat et al, 2009). Zn-sorbed talc was prepared by adding 200 mg talc (Sigma-Aldrich, Nr.…”
Section: Exafs Reference Spectramentioning
confidence: 99%
“…Assuming that Zn carbonates are formed by supergene alteration of sphalerite in these locations, the significant theoretical fractionation between Zn(H 2 O) 2+ 6 complex and Zn carbonates could suggest that Zn is quantitatively reincorporated in precipitating secondary carbonates. The precipitation of Zn carbonate in low temperature environment is attested by, e.g., Jacquat et al (2008), who have found hydrozincite in heavily Zn polluted carbonated soils. The study of Pašava et al (2014) investigated zinc isotope composition in minerals at La Florida mine (Basque Cantabrian Basin, Spain), where very intense supergene alteration leads to the formation of hydrozincite, smithsonite and hemimorphite.…”
Section: Geochemical Implications For Natural Samplesmentioning
confidence: 99%
“…Several crystalline phases containing Zn have been identified in contaminated soils. Commonly observed minerals include zinc carbonate minerals (smithsonite ZnCO 3 and hydrozincite Zn 5 (CO 3 ) 2 (OH) 6 ) and zinc silicate minerals like hemimorphite (Zn 4 Si 2 O 7 (OH) 2 ·H 2 O) (Boni et al, 2005;Balassone et al, 2008;Jacquat et al, 2008Jacquat et al, , 2009. In acid mine drainage systems and smelter-impacted soils, zinc-iron and zinc-aluminium spinels namely franklinite (ZnFe 2 O 4 ) and gahnite (ZnAl 2 O 4 ) are found as well as the zinc oxide zincite (ZnO) (Kucha et al, 1996;Hochella et al, 1999;Sobanska, 1999;Juillot et al, 2003;Jacquat et al, 2009;Juillot et al, 2011).…”
Section: Introductionmentioning
confidence: 99%